Redefining access for success in Engineering extended programmes - Machika, Pauline (South African Journal of Higher Education, 2016)
Since 2006, there has been a shift in the debate from ‘alternative access to higher education’ to ‘access for success’ when registering for extended curricula studies. Currently trends indicate that more students take longer than 3+1 years to obtain their extended curricula qualification, despite the accompanying holistic academic support offered by higher education institutions. The purpose of the article is to indicate that it is vital that students pass all first-year subjects if access for success is to be achieved. A descriptive, exploratory study was undertaken using quantitative data from four cohorts of first-year students enrolled for the National Diploma in Engineering at the University of Johannesburg. Results indicated that students who passed all their subjects in the first year were able to complete their studies within the minimum period. This research highlights the need to redefine the term ‘access for success’ within the South African higher education environment.